Faktory ovlivňující přirozenou úrokovou míru na straně poptávky - Černý, Jakub (2009)
I endeavour to identify the factors that influence the capital profitability in this work. So I study the usual objectives of the firms and how they reach these objectives, inquire into the ways how the firms assess their activities and describe the modern history of these assessments and then describe possibilities of the formation of the prices. I analyse the investing in human capital extra. And I endeavour to detect the influence of credits and market disequilibriums on investments.